Unraveling the impact of political control and earnings management on corporate performance in Indonesia - Yusuf, Muhammad; Ismail, Tubagus; Taqi, Muhammad; Soleha, Nurhayati (Edelweiss Applied Science and Technology, 2025)
In emerging places like West Java, Indonesia, agricultural production is crucial for economic stability and food security. To determine which variables significantly affect agricultural production, this research used a linear regression model. Educational attainment, years of agricultural experience, land ownership status, and rice field type are some of the factors that this study examines using survey data collected from farmers in West Java as a pilot project. The model found that the most important variables positively affecting yields were education level, type of rice field, and farming experience, with an R² value of 0.184 and an RMSE of 24.238. On the other hand, factors like land ownership and membership in farmer associations had little to no impact, if any at all, highlighting the need to reconsider long-standing forms of assistance. The results stress the need to promote the use of alternative agricultural methods adapted to specific regions and to enhance farmers’ access to education and training. Soil quality, weather, and availability of agricultural technology are additional pieces of information that might enhance the model’s predictive capabilities. To improve comprehension and applicability, future studies should consider using more sophisticated modeling methods and larger datasets. With these findings in hand, stakeholders and legislators may implement concrete suggestions to improve farming methods and secure long-term production in West Java and beyond.